The Kalibapi's 1944 Lakambini popularity contest during the Japanese occupation of Iloilo city - Redison, Frances Anthea R. (Philippine Studies: Historical and Ethnographic Viewpoints, 2022)
In 1944 the Kapisanan sa Paglilingkod sa Bagong Pilipinas (Kalibapi), a socio-civic organization founded during the Japanese occupation, organized the Miss Lakambini beauty contest in Iloilo for the Japanese Military Administration (JMA) propaganda campaign. Forty-one women competed for the title during the Cultural and Industrial Rally to promote the supposed harmonious relationship between the Ilonggos and the JMA and portray normalcy during the war. The beauty contest affirms the complexity of the issue of wartime collaboration in Iloilo as the Ilonggo elites simultaneously cooperated with the Japanese and supported the guerrilla movement in its "lie low policy."